Bioassay-Guided Interpretation of Antimicrobial Compounds in Kumu, a TCM Preparation From Picrasma quassioides’ Stem via UHPLC-Orbitrap-Ion Trap Mass Spectrometry Combined With Fragmentation and Retention Time Calculation - Hu, Haibo; Hu, Changling; Peng, Jinnian; Ghosh, Alokesh Kumar; Khan, Ajmal; Sun, Dan; Luyten, Walter (Frontiers in Pharmacology, 2021)
The stem of Picrasma quassioides were recorded as a famous traditional Chinese medicine, Kumu, with the effect on microbial infection, anti-inflammation, fever, dysentery, etc. At present, Kumu is widely used in China and was developed as different medicines, even for injection (Kumu zhusheye), with the main application for combating infections. However, the chemical basis for its antimicrobial activity has still not been elucidated. To exam the ac-tive chemicals, its stem was extracted to perform bioassay guided purification against Staphylococcus aureus and Escherichia coli. In this study, two columns (normal and reverse-phase) were used for speedy bio-assay guided isola-tion from Kumu, and the active peaks were collected and identified via an UHPLC-Orbitrap-Ion Trap Mass Spec-trometer, combined with MS fragmenter and Chromgenius. For identification, the COCONUT database (largest database of natural products) and a manually built PQ database were used, in combination with prediction and calculation of mass fragmentation and retention time to better infer their structures, especially for isomers. Moreo-ver, three standards were analyzed under different conditions for developing and validating the MS method. 25 active compounds were identified, including 24 alkaloids and 1 triterpenoid against S. aureus, whereas only β-carboline-1-carboxylic acid and picrasidine S were active against E. coli. Here, the good antimicrobial activity of 18 chemicals was reported for the first time. Furthermore, the spectrum of three abundant β-carbolines was as-sessed via their MIC50 and MBC against various human pathogens. All of them exhibited strong antimicrobial activities with good potential to be developed as antibiotics. This study clearly showed the antimicrobial chemical basis of Kumu and the results demonstrated that HRMS coupled with MS fragmenter and Chromgenius was a powerful tool for compound analysis which can be used for other complex samples. And all the beta-carbolines reported here are important lead compounds in antibiotic discovery.